Luz, câmara, acção: orientações para a filmagem da actividade real de trabalho - Liliana Cunha; Rita Gil Mata; Fernanda Correia (Universidade do Porto, 2006)
During a seminar that took place at FPCEUP[1], Christian Lascaux, a director that develops his activity in ergonomic and work psychology teams at CNAM[2], CNRS[3] and Paris 8 University[4], we acquired a different view of video utilisation in activity analysis: resorting to film helps not only to assist the observation of the work situation, but also supports the development of other work analysis methods, offering an opportunity for the workers being confronted with their work practices, as shown by the self-confrontation method (Clot et al. 2000).Multiple questions arise at the moment of filming: how and when to use de video? What is the necessary material? How long should it be?The answer to these questions integrates the recognition that it is not possible to present a unique answer, which will depend on the specific context, the request presented, the subjacent objectives and the methodological options assumed.